Determination of Pathotypes from Indonesian Xanthomonas oryzae Pv. Oryzae Population causing Bacterial Leaf Blight and their Reactions on Differential Rice - Suryadi, Yadi; Samudra, I Made; Priyatno, Tri Puji; Susilowati, Dwi Ningsih; Lestari, Puji; Fatimah,; Kadir, Trini Suryani (Makara Journal of Science, 2016)
The objective of this work was to study the virulence of 15 Xanthomonas oryzae pv. oryzae (Xoo) isolates collected in three provinces in Indonesia (North Sumatra, South Sumatra, and South Sulawesi) based on five Indonesian differential rice genotypes and 10 near isogenic lines (NILs) that have been known to differ in their resistance to bacterial leaf blight (BLB), in a greenhouse assessment. In addition, this study also aims to monitor the responses of 31 rice genotypes (21 NILs, five differentials, five improved cultivars) to BLB disease in a field experiment. The 15 isolates showed different virulence patterns on the NILs’genotypes with a single resistance gene indicating the pathogen diversity. Eight different pathotypes were present, as demonstrated by a particular virulence pattern of each isolate on the genotypes. Determination of Xoo pathotype revealed that Xoo pathotypes responded differently based on their reaction to NILs and Indonesian differential genotypes. The field assessment demonstrated the incidence and severity of BLB disease on rice genotypes ranging from 25% to 100% and 5.5% to 72.91%, respectively, while the mean disease index ranged from 1.15% to 72.9%. The disease response varied among rice genotypes. IRBB50 (Xa4+xa5), IRBB51 (Xa4+xa13), IRBB52 (Xa4+Xa21), IRBB53 (Xa4+Xa21), IRBB56 (Xa4+xa5+xa13), IRBB57 (Xa4+xa5+Xa21), IRBB59 (Xa4+xa13+Xa21), IRBB64 (Xa4+xa5+Xa7+Xa21), IRBB66 (Xa4+xa5+Xa7+xa13+Xa21), IRBB7(Xa7), Angke (Xa4+xa5) and Code (Xa4+Xa7) were revealed to be highly resistant to the BLB pathogen. These genotypes have potential as genetic material for the pyramiding of several resistance genes for the development of rice resistance to BLB disease in Indonesia.